SINIF ÖĞRETMENLERİNİN ÖZEL ÖĞRENME GÜÇLÜĞÜ OLAN ÖĞRENCİLERİN EĞİTSEL DEĞERLENDİRME VE EĞİTİMSEL MÜDAHALE SÜRECİNDE GÖRÜŞ VE UYGULAMALARI - KURUYER, Hayriye Gül; ÇAKIROĞLU, Ahmet (Electronic Turkish Studies)
The purpose of the current study is to investigate primary school teachers' opinions and practices related to the process of educational evaluation and intervention. To this end, the study employed the grounded theory methodology, one of the qualitative research methods. There are eight primary school teachers in the study group of the current research. To select the participating teachers, the criterion sampling method was used. The data were collected through semi-structured interviews and unstructured non-participant observations. The data collected in the study were evaluated by using the continuous comparison method. Open codes were attempted to be reached within the context of the continuous comparison method. In order to reach open codes, during the transcription process the note-taking and underlining techniques were used. By examining the similarities and differences between the codes, categories were attained. The analysis yielded four categories; specific learning difficulty, problems, tasks and process. The findings of the current study show that the understanding of the concept of specific learning difficulties varies from teacher to teacher. It was concluded that the understanding of the concept of specific learning difficulties is shaped on the basis of the teacher's background and practices. It was observed that the teacher's perception and knowledge directly and indirectly affect whether or not a student is diagnosed with specific learning difficulties and how much effort is made to overcome these difficulties. The current research suggests that the primary school teachers have both a lack of knowledge about educational evaluation and the preparation of educational intervention programs, and hold conceptual-factual fallacies that make evaluation more difficult. Moreover, it was observed that they experienced some difficulties in the process of developing and applying educational intervention programs.